Controlling Macroscopic Phase Separation of Aqueous Two-Phase Polymer Systems in Porous Media. (October 2019) - Pereira, David Y.; Wu, Chloe M.; Lee, So Youn; Lee, Eumene; Wu, Benjamin M.; Kamei, Daniel T.
In previous work, our group discovered a phenomenon in which a mixed polymer–salt or mixed micellar aqueous two-phase system (ATPS) separates into its two constituent phases as it flows within paper. While these ATPSs worked well in their respective studies to concentrate the target biomarker and improve the sensitivity of the lateral-flow immunoassay, different ATPSs can be advantageous for new applications based on factors such as biomarker partitioning or biochemical compatibility between ATPS and sample components. However, since the mechanism of phase separation in porous media is not completely understood, introducing other ATPSs to paper is an unpredictable process that relies on trial and error experiments. This is especially true for polymer–polymer ATPSs in which the characteristics of the two phases appear quite similar. Therefore, our group aimed to develop semiquantitative guidelines for choosing ATPSs that can phase separate in paper. In this work, we evaluated the Washburn equation and its parameters as a potential mathematical framework to describe the flow behavior of polymer–salt and micellar ATPSs in fiberglass paper. We compared bulk phase fluid characteristics and identified the viscosity difference between the phases as a key determinant of the potential for phase separation in paper. We then used this parameter to predict the phase separation capabilities of polyethylene glycol (PEG)–dextran ATPSs in paper and control the composition of the leading and lagging phases. We also, for the first time, successfully demonstrated the phase separation phenomenon in hydrogels, thereby extending its application and potential benefits to an alternative porous medium.